Desistance from Crime Over the Life Course, South Carolina, 2005-2017 - Lattimore, Pamela K. ([Verlag nicht ermittelbar], 2021)
The current study focused on 479 men and women from South Carolina who were enrolled as participants in the Serious and Violent Offender Reentry Initiative (SVORI) multi-site program evaluation shortly before prison release in 2004 or 2005. The original SVORI data suggested that the South Carolina respondents were similar to the multi-site sample with "committed to not going back to prison" as the most common reason for desisting and using drugs or alcohol as the most common reason for persisting. The goals of the current study were to (1) update information on the current status of these individuals across multiple domains (e.g., housing, employment, substance use); (2) gather additional administrative recidivism data to examine long-term offending; and (3) acquire information about the factors individuals associated with their decisions to desist from criminal activity, as well as circumstances associated with renewed criminal activity or desistence. Interviews were conducted with those that the study team were able to locate and additional administrative arrest and incarceration data were acquired for the full sample, providing recidivism follow-up over at least a 10-year period. Official administrative data were obtained from the South Carolina Law Enforcement Division (rearrests) and South Carolina Department of Corrections (reincarcerations). Arrest data span the entire arrest history (from first arrest through December 2015); reincarceration data span the period between the SVORI study prison release in 2005 and 2006 through June 2014. These data were obtained for the full sample of 479 South Carolina SVORI participants. Three components of interview data were collected. Desistance study interview data: 1 wave of in-person interviews was conducted with 208 study subjects who consented to participate in an interview. The research team used computer-assisted personal interviewing (CAPI) to administer the survey, and interviews were conducted from September 2016 through March 2017. Life event data: The Life Events Calendar (LEC) is a tool used in qualitative and quantitative research to gather retrospective information about a person's life, experiences, and history. The approach is based on autobiographical memory and how entering events on a calendar or page help facilitate memory recall. LECs typically encompass periods of 5 years or less; this study's LEC covered a 10- to 12-year span to allow analysis since last contact with the study cohort. Data were collected from the 208 subjects who consented to be interviewed. SVORI interview data: This inventory includes files with select baseline and outcome data (e.g., self-reported employment, drug use, criminal behavior) for desistance study subjects who responded to follow-up interviews at Wave 2 (3-month), Wave 3 (9-month), and Wave 4 (15-month). This collection of administrative and interview data is organized into 14 data parts. Demographic data includes information on age, gender, race, and education.